2019
DOI: 10.1177/0305735618824987
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the inner radio: The mental control of musical imagery in everyday environments

Abstract: How easily can people tune their inner radio? Musical imagery-hearing music in your mind-is common but little is known about people's ability to control their musical imagery in daily life. A recent model distinguishes between initiation (starting musical imagery) vs. management (modifying, stopping, or sustaining musical imagery) as facets of control, and the present research examined people's ability to use these two forms of control in daily life. For seven days, students (29 music students, 29 non-music st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…This resulted in the exclusion of the very first attempts to utilize modern psychological methods to study INMI (Bennett, 2003;Kellaris, 2001Kellaris, , 2003, a book chapter describing an early induction experiment (Hemming, 2009), and three doctoral theses (Floridou, 2015;Liikkanen, 2018;McNally-Gagnon, 2016). Some studies that referred to INMI, but did not present new empirical results related to it, were also excluded (Bailes, 2006;Cotter & Silvia, 2019;Huovinen & Tuuri, 2019). One paper that we retained following the initial literature search (Bailes, 2007) made no explicit differentiation between INMI and voluntary musical imagery, but is discussed in the present review on the basis of its seminal contribution in establishing a methodology for capturing musical imagery experiences in everyday life.…”
Section: Paper Selection and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in the exclusion of the very first attempts to utilize modern psychological methods to study INMI (Bennett, 2003;Kellaris, 2001Kellaris, , 2003, a book chapter describing an early induction experiment (Hemming, 2009), and three doctoral theses (Floridou, 2015;Liikkanen, 2018;McNally-Gagnon, 2016). Some studies that referred to INMI, but did not present new empirical results related to it, were also excluded (Bailes, 2006;Cotter & Silvia, 2019;Huovinen & Tuuri, 2019). One paper that we retained following the initial literature search (Bailes, 2007) made no explicit differentiation between INMI and voluntary musical imagery, but is discussed in the present review on the basis of its seminal contribution in establishing a methodology for capturing musical imagery experiences in everyday life.…”
Section: Paper Selection and Data Analysismentioning
confidence: 99%
“…However, the present evidence demonstrates that repetitive INMI is seldom perceived as intrusive, and therefore we do not believe it should be labeled as such. In addition, the use of the term "involuntary" should be clearly defined and explained to research participants, in terms of whether it is being used to describe the initiation of the imagery episode, subsequent management of the experience, or both (see Cotter & Silvia, 2019). References to the model of the INMI process presented in Fig.…”
Section: Call For Rigor and Repetitionmentioning
confidence: 99%
“…In daily life, people do not frequently initiate musical imagery (Beaty et al, 2013; Bailes, 2015; Cotter et al, 2018)—when asked if they started an episode of musical imagery on purpose, people report doing so approximately 25% of the time (Cotter et al, 2018). Interestingly, when people are asked to initiate an episode of musical imagery in everyday life, both musicians and non-musicians report being able to do so most of the time (61%; Cotter and Silvia, 2018), and all participants were able to initiate musical imagery at least once during the study. Even though not the dominant way musical imagery begins, both musicians and non-musicians do report intentionally initiating musical imagery occasionally in their everyday life and are generally capable of initiating musical imagery when instructed to do so.…”
Section: Major Approaches To Mental Control In Everyday Musical Imagerymentioning
confidence: 99%
“…One study has also investigated self-reported management ability (Cotter and Silvia, 2018). In this study, participants were asked to perform five manipulations to their musical imagery—changing the tempo, key, vocalist’s gender, primary instrument, and entire song.…”
Section: Major Approaches To Mental Control In Everyday Musical Imagerymentioning
confidence: 99%
See 1 more Smart Citation